VARIABILITY IN YIELD AND VOLATILE CONSTITU ENTS OF CYM B OPO GON JAWARANCU SA (JONES) SCHULT FROM PAKISTAN: Short Communication - Riaz, M; Ahmad, Rafi; Chaudhary, F M (Biological Sciences - PJSIR, 2001)
Cymbopogon jawarancusa (Gramineae) (Kirtikar and Basu 1993), locally known as Khavigrass is a perfumed grass widely distributed in the Himalayan region upto 2438 m from Kash mir to Assam. It also grows abundantly in the arid-zones of Pakistan (Sultan and Stewart 1958), especially in Mianwali , Jhang, Muzaffargarh and Campbellpur Districts . The genus Cymbopogon is known for the presence of economically important compounds such as citral, citronellol, geraniol, piperitone and methyl eugenol which are highly valued as flavoring agents and in the pharmaceutical industry. Although a lot of work has been carried out on the chemical composi tion of the essential oils (Saeed et al 1978; Thappa et al 1979; Mathela and Joshi 1981; Shahi and Sen 1989; Rao et al 1992; Beauchamp et al 1996) of this genus, yet this local variety of Punjab has not been studied earlier.